DNA polymerase β prevents AID-instigated mutagenic non-canonical mismatch DNA repair - Mahnoush Bahjat; Stratigopoulou, Maria; Pilzecker, Bas; Van Dam, Tijmen P; Mobach, Simon; Bende, Richard J; Carel Jm Van Noesel; Jacobs, Heinz E; Guikema, Jeroen E (bioRxiv, 2020)
In B cells, the error-prone repair of activation-induced cytidine deaminase (AID)-induced lesions in immunoglobulin variable genes cause somatic hypermutation (SHM) of antibody genes. Due to clonal selection in the germinal centers (GC) this active mutation process provides the molecular basis for antibody affinity maturation. AID deaminates cytosine (C) to create uracil (U) in DNA. Typically, the short patch base excision repair (spBER) effectively restores genomic U lesions. We here demonstrate that GC B cells actively degrade DNA polymerase β (Polβ), resulting in the inactivation of the gap-filling step of spBER. Consequently, lesions instigated by AID, and likely other base damages, are channeled towards mutagenic non-canonical mismatch repair (mncMMR), responsible for the vast majority of mutations at adenine and thymine (A:T) bases. Apparently, GC B cells prohibit faithful spBER, thereby favoring A:T mutagenesis during SHM. Lastly, our data suggest that the loss of Polβ relates to hypoxia that characterizes the GC microenvironment.